THE INFLUENCE OF WORD OF MOUTH, PRODUCT QUALITY AND SALES PROMOTION ON THE PURCHASE DECISION OF BRAND SHAMPOO PRODUCTS HEAD & SHOULDERS BY THE COMMUNITY IN JEUMPA DISTRICT REGENCY BUREAUCRACY - Nazifa Hafiza; T. Edyansyah; Chalirafi; Heriyana (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to review the impact of word-of-mouth communication, product quality, and sales promotion activities on the decision to buy Head & Shoulders brand shampoo by people in the Jeumpa area, Bireuen Regency. The research approach utilizes multiple linear regression analysis, including hypothesis testing using SPSS software. The respondent selection technique used the convenience sampling method, with 100 participants who had purchased Head & Shoulders shampoo at least once or twice. The type of information used is in the form of quantitative data, which is information in the form of numbers that measure one or more variables in the population or sample being studied, either through numerical values or statistical calculations. The source of information used is primary data obtained directly from participants or study locations. The findings showed that separate word-of-mouth communication had a positive or significant influence on purchasing decisions, product quality separately also had a positive or significant impact on purchasing decisions, while sales promotions separately had no or insignificant influence on the purchase decision of Head & Shoulders branded shampoos, while the rest were influenced by other variables.